PCSK9 inhibitors and cardiovascular outcomes. (2nd January 2020) - Steffens, Daniel; Bramlage, Peter; Scheeff, Céline; Kasner, Mario; Hassanein, Adel; Friebel, Julian; Rauch-Kröhnert, Ursula
ABSTRACT: Introduction : Dyslipidemia, particularly elevated low-density lipoprotein cholesterol (LDL-C), is a key risk factor for atherosclerotic cardiovascular disease (ASCVD), and lipid-lowering drugs are beneficial for the primary and secondary prevention of cardiovascular (CV) disease. While statins are clear first-line drugs, new drug developments such as proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors have been shown to improve cardiovascular outcomes when added to statins. Evolocumab reduced the risk of cardiovascular events in patients with ASCVD when added to maximally tolerated statin therapy (± ezetimibe), and recent data from the ODYSSEY OUTCOMES trial indicate that alirocumab added to maximally tolerated statin therapy (± other lipid-lowering drugs) reduces the risk of cardiovascular events in patients with a recent acute coronary syndrome. In this article the authors review the available data on the effect of PCSK9 inhibitors on cardiovascular outcomes. Areas covered : This article reviews the available data on the effect of PCSK9 inhibitors on CV outcomes. Relevant papers were identified from a search of PubMed/Medline and the Cochrane Central Register of Controlled Trials (CENTRAL). Expert opinion : The authors conclude that PCSK9 inhibitors provide substantial and durable reductions in LDL-C levels and improve cardiovascular outcomes.